2018
DOI: 10.7567/apex.11.102001
|View full text |Cite
|
Sign up to set email alerts
|

Plasmonic transfer of near-field light from subwavelength objects through a gold-nanorod chain

Abstract: Plasmonics-based nanoimaging techniques have recently attracted significant attention owing to their ability to confine light to the nanoscale for super-resolution imaging. A recent report has theoretically predicted that a plasmonic nanolens, a well-designed array of metallic nanorod chains, can produce a magnified color image of subwavelength objects through a plasmonic transfer of near-field light as a new class of nanoimaging technique. In this study, we fabricate a gold-nanorod chain through a self-assemb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
(29 reference statements)
0
4
0
Order By: Relevance
“…In order to correctly fabricate the nanorod chains, we started with a theoretical optimization of the fabrication parameters. For this purpose, we first calculated the near-field intensity spectrum of an isolated single silver nanorod by the finite-difference time-domain (FDTD) method, under the similar conditions that we used in our previous report for a gold nanorod 15 . In the process of optimizing the size of individual nanorods, we found that a 150-nm-long silver nanorod with 60 nm diameter shows plasmon resonance in the center of the visible range as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In order to correctly fabricate the nanorod chains, we started with a theoretical optimization of the fabrication parameters. For this purpose, we first calculated the near-field intensity spectrum of an isolated single silver nanorod by the finite-difference time-domain (FDTD) method, under the similar conditions that we used in our previous report for a gold nanorod 15 . In the process of optimizing the size of individual nanorods, we found that a 150-nm-long silver nanorod with 60 nm diameter shows plasmon resonance in the center of the visible range as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This is the reason why a plasmonic nanolens has not yet been experimentally demonstrated. In order to show the experimental feasibility of a plasmonic nanolens, we first started with a simplified structure to prove image transfer through a nanorod chain 15 . In our previous study, we demonstrated that a single gold nanorod chain can transfer near-field light originated from a nano-sized optical source of quantum dots (QDs) to a distance much larger than the diffraction limit of light 15 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations